Optically controlled electroresistance and electrically controlled photovoltage in ferroelectric tunnel junctions - Wei Jin Hu (Nature Portfolio, 2016)
Tunnelling electroresistance is the variation of resistance of a thin-film junction with the polarization state of its ferroelectric tunnel barrier. Here the authors demonstrate a large light-modulated tunnelling electroresistance and a hysteretic photovoltaic effect in a complex oxide heterostructure.